(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Senevskaya N. Gender approach in secondary education (to study drama material Lesia Ukrainka in grade 10). In the article gender approach is characterized in secondary education that consists both in circulating of present gender stereotypes and in advancement of ideas of gender equality. The gender analysis of dramatic poems of Lesia Ukrainian as one of facilities of correction of process of socialization is described youth depending on sex.